Profound and Sexually Dimorphic Effects of Clinically-Relevant Low Dose Scatter Irradiation on the Brain and Behavior - Kovalchuk, Anna; Mychasiuk, Richelle; Muhammad, Arif; Hossain, Shakhawat; Ilnytskyy, Yaroslav; Ghose, Abhijit; Kirkby, Charles; Ghasroddashti, Esmaeel; Kolb, Bryan; Kovalchuk, Olga (Frontiers in Behavioral Neuroscience, 2016)
Irradiated cells can signal damage and distress to both close and distant neighbors that have not been directly exposed to the radiation (naïve bystanders). While studies have shown that such bystander effects occur in the shielded brain of animals upon body irradiation, their mechanism remains unexplored. Observed effects may be caused by some blood-borne factors; however they may also be explained, at least in part, by very small direct doses received by the brain that result from scatter or leakage. In order to establish the roles of low doses of scatter irradiation in the brain response, we developed a new model for scatter irradiation analysis whereby one rat was irradiated directly at the liver and the second rat was placed adjacent to the first and received a scatter dose to its body and brain. This work focuses specifically on the response of the latter rat brain to the low scatter irradiation dose. Here, we provide the first experimental evidence that very low, clinically relevant doses of scatter irradiation alter gene expression, induce changes in dendritic morphology, and lead to behavioral deficits in exposed animals. The results showed that exposure to radiation doses as low as 0.115 cGy caused changes in gene expression and reduced spine density, dendritic complexity, and dendritic length in the prefrontal cortex tissues of females, but not males. In the hippocampus, radiation altered neuroanatomical organization in males, but not in females. Moreover, low dose radiation caused behavioral deficits in the exposed animals. This is the first study to show that low dose scatter irradiation influences the brain and behavior in a sex-specific way.